Etika dan Penyelenggaraan Pelayanan Publik ( Analisis Literasi Etika dan Penyelenggaraan Pelayanan Publik ) - Nimas Arum P.S; Jamilatus Sarifah; Daffa Fawaz Musafa (Jurnal Akuntan Publik, 2023)
Public service is all a series of activities in the framework of fulfilling basic needs in accordance with the basic rights of every citizen and resident over goods, services and or administrative services that have been provided by service providers related to the public interest. The community as customers have needs and expectations for the performance of professional public service providers. The task of the Central Government and Regional Governments is to provide public services that are able to satisfy their people. The implementation of decentralization and regional autonomy policies in Indonesia has resulted in local governments having the responsibility and authority to determine minimum service standards. The fundamental problem in the process of public service in Indonesia is about ethics. The absence of universal standards regarding norms or ethics and sanctions that regulate specifically for violations committed by officials in public services.